Disordering 'Order'; Learning How to Eat in Recovery from an Eating Disorder - Plant, Angela (Université d'Ottawa / University of Ottawa, 2014)
This ethnographic study explores the everyday experiences of recovery from an eating disorder. The fieldwork took place in Toronto and Ottawa, Ontario, Canada over a 4 month period in 2013. It involved interviews and participant observation with 12 women who were in various stages of recovery, as well as a reflexive component based on the researcher’s own experiences of recovery. The aim of the study was to uncover what it meant to recover from an eating disorder in terms of everyday eating. Specifically, “How did those in recovery learn to eat?” and “Were they learning to eat in an ‘ordered’ way?” The findings reveal there is a complex and challenging route to ‘ordered’ eating in Canadian society. Contemporary dietary practices compete for authority and popularity while simultaneously offering completely different ways of relating to and knowing food. Those in recovery are therefore lost in a maze of options telling them how to eat ‘right’ which further isolates them. The study shows however that learning to eat in recovery is not about eating in an ‘ordered’ way but more so about situating one’s self in contexts and within relationships; moving with food. It suggests that a way of moving forward in recovery is to let go of the correct ‘order’ to eating and to move forward in its continual making and unmaking.
Keywords: Eating Disorder; Recovery; Nutrition; Learning